Використання Chaetomium cochliodes Palliser для підвищення врожайності сої (Glycine max (L.) Merr) - Kopilov, E.P.; Nadkernichny, S.P.; Melnik, A.I.; Usmanova, G.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
For the first time it was determined that saprophytic fungus Chaetomium cochliodes 3250 is able to produce phytohormone substances (auxins, cytokinins, gibberellins) on the Rolene-Tom medium. The usage of the fungus for presowing treatment of soybean seeds (Glycine max (L.) Merr) promoted for intense growth and development of soybean plants and significant rise of the harvest – on 28.6 % in comparison with control variant. The most effective was the complex usage of C. cochliodes 3250 and Bradyrhizobium japonicum 2490. C. cochliodes 3250 had a great influence on absorption of microelements Cu, Fe, Mn by the soybean plants from soil. Their maintenance in seeds rised on 24.6; 11.0; 16.8 % and the maintenance of phosphorus rised on 13.8 % comparing to control.